Mitophagy regulation mediated by the Far complex in yeast - Furukawa, Kentaro (Autophagy, 2021)
Mitochondrial autophagy (mitophagy) selectively degrades mitochondria and plays an important role in mitochondrial homeostasis. In the yeast Saccharomyces cerevisiae, the phosphorylation of the mitophagy receptor Atg32 by casein kinase 2 is essential for mitophagy, whereas this phosphorylation is counteracted by the protein phosphatase Ppg1. Although Ppg1 functions cooperatively with the Far complex (Far3, Far7, Far8, Vps64/Far9, Far10 and Far11), their relationship and the underlying phosphoregulatory mechanism of Atg32 remain unclear. Our recent study revealed: (i) the Far complex plays its localization-dependent roles, regulation of mitophagy and target of rapamycin complex 2 (TORC2) signaling, via the mitochondria- and endoplasmic reticulum (ER)-localized Far complexes, respectively; (ii) Ppg1 and Far11 form a subcomplex, and Ppg1 activity is required to assemble the sub- and core-Far complexes; (iii) association and dissociation between the Far complex and Atg32 are crucial determinants for mitophagy regulation. Here, we summarize our findings and discuss unsolved issues.